S59 Clinical neurophysiology in movement disorders - Regidor, Ignacio (Clinical neurophysiology, 2017)
Movement disorders are physiologically studied based on three principles; 1. relation between movements and brain activities, 2. excitability and inhibitory mechanisms of motor cortices, and 3. sensorimotor integration. Regardless of voluntary or involuntary movements, the study on how the movement in question is related to brain activities provides an important information as to its pathophysiology. This can be studied by jerk-locked averaging of electroencephalogram or magnetoencephalogram in case of involuntary movements and movement-related cortical potentials for voluntary movements, change of cortical rhythmic activities in relation to movement (event-related desynchronization or synchronization), cortico-muscular coupling (coherence), and neuroimaging techniques such as PET, SPECT and fMRI. Excitability and inhibitory mechanisms of motor cortices can be studied by applying transcranial magnetic stimulation. Positive and negative myoclonus of cortical origin is related to abnormal hyperexcitability of the positive and negative components, respectively, of the primary motor cortex (M1). Focal dystonia is associated with impairment of inhibitory mechanisms in M1. The simplest form of abnormal sensorimotor integration is cortical reflex myoclonus. In the choice reaction time task, contingent negative variation is reduced in a task-specific way in focal dystonia. Effect of movement on somatosensory processing (gating) is abnormal immediately before the movement onset in focal dystonia, again in a task-specific way. Daily activities like gait can be studied by SPECT which does not require fixation of the subject’s head during the task performance.